Саирхе — культовый центр древней Колхиды - Брагвадзе, Д.З.; Церетели, М.В. (Археологія, 1997)
Статья посвящена рассмотрению украшений головного убора из погребальных комплексов могильника Саирхе в Восточной Колхиде. Могильник Саїрхе, розташований на лівому березі р. Квирила у східній частині історичної Колхиди, є однією з найвизначніших археологічних пам’яток Грузії.
У статті розглянуто деякі типи прикрас, що надходили до складу головного убору у жіночих похованнях цього могильника, зокрема — діадеми, сережки, скроневі підвіски. На підставі аналізу цих знахідок у контексті космогонічних уявлень населення стародавньої Колхіди зроблено висновок щодо соціального статусу похованих у могильнику. Це були жінки, які супроводжували головного небіжчика — правителя, в руках якого було сконцентровано як світську, так і духовну владу. При цьому, діадеми інтерпретуються як знаки світської функції правителя, а сережки у формі напівмісяця — духовної. The paper is devoted to the analysis of adorments on a head-dress from burial complexes of the Sairche sepulchre in eastern Kolchida. This sepulchre situated on the left bank of the river Kviril in the eastern part of historical Kolchida is one of the most significant archaeological monuments in Georgia.
Some types of adornments which belonged to a head-dress and were found in women’s graves of this sepulchre are described in the paper, particularly: diadems, ear-rings, temple pendants. Proceeding from the analysis of these findings in the aspect of cosmogonic views of population in ancient Kolchida the social state of the women buried is determined. They were women who accompanied the main deceased, a ruler, in whose hands there was concentrated both temporal and clerical power. Diadems are interpreted as a symbol of the temporal power of a ruler, and ear-rings shaped as a half-moon demonstrate clerical functions.